Floristic and Forest Structural Study in Batangtoru Watershed, North Sumatra - Sambas, Edy Nasriadi; Siregar, Mustaid (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTA Forest ecology research has been done in Batangtoru watershed, North Sumatra to determine the speciesÂ composition and vegetation structure. The study was conducted by using plots in four locations: Purnama,Gerhana, Kejora, and Teluk Nauli. A total of 387 species in 184 genera and 77 families were found. TheÂ species richness of trees (dbh >10 cm) was 192 species in 116 genera and 55 families, the richness of saplings(dbh 2 - 10 cm) was 211 species in 111 genera and 55 families, while the richness of seedlings (dbh <2 cm)Â was 153 species in 95 genera and 50 families. Tree density ranged from 850â1,700 individuals/ ha, while basalarea was around 66.76 to 104.54 m2/ha. The forest canopy at Purnama and Gerhana plots was relatively similar,Â forming three layers, while the Kejora and Teluk Nauli plots were simpler with only two canopy layers. Basedon a principal components analysis of tree species, the forests in the research area tended to form threeÂ community types: 1) forest dominated by Pentaphylacaceae, 2) mixed dipterocarp forest, and 3) forest garden,or natural forest communities enriched with a variety of economically valuable forest tree species andÂ therefore classified as an agroforestry system.Keywords : Floristic, structure, forest community type, Batangtoru watershed, North Sumatra